Nickel-iron layered silicate nanomembrane as efficient electrocatalyst for oxygen evolution reaction in alkaline media. (15th January 2023) - Zhang, Jing; Li, Zhaolong; Bai, Guo; Wang, Qingbing; Zhang, Jin; Wang, Wei; Zhou, Liujiang; Yi, Jiang; Ma, Zhiyuan
Graphical abstract: Highlights: Nickel-iron layered silicate was prepared by coprecipitation-hydrothermal method. Fe-containing samples outperforms commercial RuO2 in OER activity. The catalyst exhibits favorable OER stability in alkaline environment. Fe doping changed the OER pathway of nickel layered silicate. Abstract: Nickel-iron bimetal compounds have shown to be efficient electrocatalysts for the oxygen evolution reaction (OER) in alkaline environment. Here, we report the outstanding OER performance of an iron doped nickel layered silicate (Ni1- x Fe x )3 Si2 O5 (OH)4 ( x  = 0, 0.1, 0.2, 0.3 and 0.4), which was synthesized via a combined co-precipitation and hydrothermal method. The doping Fe ions are found to have a stronger adsorption effect on the *O intermediate, thereby reducing the energy barrier for the potential determining step *OH → *O, and as a result greatly enhance the OER activity of nickel layered silicate. At Fe doping concentration of 30 mol%, a minimum OER overpotential of 286 mV is achieved at the current density of 10 mA cm −2 without IR correction, 86 mV lower than that of undoped catalyst. Moreover, the catalyst maintains favorable OER stability over a 24-hour chronopotentiometry test in 1 M KOH. This work provides insights into exploration and design of metal silicate-based OER catalysts.